Family correspondence of famous Ukrainians as a source of prosopographic information (on the example of epistolary communications of the Chykalenkos). - Starovoitenko, Inna (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2025)
The aim of the study is to present the Chikalenko family correspondence, compiled in exile (1920s–1960s), as the main source for researching prosopographic stories about certain periods in the lives of famous Ukrainians, the circumstances of their life abroad, forms of self-realisation, communicative space, and interpersonal relationships. Research methodology. Based on the principles of historicism, objectivity and reliability of historical sources, the use of content analysis and synthesis methods, comparative-historical and generalisations (biographical, prosopographic). Scientific novelty. The article uses large arrays of historical sources (private correspondence) for the first time to identify prosopographic information about representatives of a well-known Ukrainian family, systematises them chronologically, and identifies the main groups of correspondence and its informational potential for achieving the goal of this study. The uniqueness of private correspondence as a historical source for reconstructing family history is noted: its representatives, important events, relationships between relatives, etc. Conclusions. Thanks to the formation and preservation by the Chikalenko family of multi-vector arrays of private correspondence, we have a solid source base for reconstructing the prosopographic portrait of a noble Ukrainian family during its division into two parts in the 1920s. Due to the Bolshevik occupation of Ukraine, part of the Chikalenko family emigrated from their homeland and settled permanently in European countries, and later in the United States, while the other part continued to live in Soviet Ukraine, and two of its members later became victims of Bolshevik terror. Thanks to the correspondence, we were able to establish the places of residence of all members of the Chikalenko family, the years and circumstances of the restoration of epistolary communications between relatives, and the nature of the relationships between them. The information in the correspondence widely reflects the forms of self-realisation of the Chikalenko family in emigration, their main occupations, physical and moral states, and their influence on their main activities. The informational potential of the correspondence recreates the history of the Chikalenko family’s lost estates: their exemplary family estate in the Kherson region and the one they acquired (in the Poltava region), and attests to the Chikalenko family’s irretrievable losses of their library, archive, and scientific collections under the Bolshevik occupation of Ukraine. The correspondence also became a source of information about the family’s growth in the 1920s and the tragic fates of individual Chikalenko family members, of whom only a few descendants remain today.